Laser-assisted management of a symptomatic anterior pharyngeal diverticulum. Issue 10 (15th August 2017) - Pujary, K; Agarwal, A C; Balakrishnan, R; Bhandarkar, A
Abstract: Background: Dysphagia is a relatively common symptom following laryngectomy. An anterior pharyngeal diverticulum is a rare cause of post-laryngectomy dysphagia. However, it is often an incidental finding on rigid telescopic examination. Methods and results: This article describes two patients with a symptomatic anterior pharyngeal diverticulum. They were treated by transoral micro-endoscopic potassium titanyl phosphate 532 nm laser assisted resection. Both patients could take feeds orally after the procedure without any difficulty. One patient died one and a half years after the procedure because of secondary lung cancer. The other patient died after three years as a result of regional recurrence. The patients were able to swallow during their survival period post treatment. Conclusion: Laser-assisted micro-endoscopic resection is a relatively safe, quick and effective procedure for the management of anterior pharyngeal diverticulum.